Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/ejn.14413
|View full text |Cite
|
Sign up to set email alerts
|

Temporal refinement of sensory‐evoked activity across layers in developing mouse barrel cortex

Abstract: Rhythmic whisking behavior in rodents fully develops during a critical period about 2 weeks after birth, in parallel with the maturation of other sensory modalities and the onset of exploratory locomotion. How whisker‐related sensory processing develops during this period in the primary somatosensory cortex (S1) remains poorly understood. Here, we characterized neuronal activity evoked by single‐ or dual‐whisker stimulation patterns in developing S1, before, during and after the occurrence of active whisking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…Furthermore, studies in sensory cortices of various rodent species have outlined a layerspecific ability for plastic adaptation reflected by changes in spine dynamics, synaptic plasticity or direct stimulation responses both during development as well as at mature ages (Jiang et al, 2007;Skibinska et al, 2000;van der Bourg et al, 2017;van der Bourg et al, 2019). These studies showed that synaptic scaling and spine dynamics are a predominant feature of supragranular layers and to a much lesser extent for infragranular layers, underscoring our data showing layer-specific AIS plasticity.…”
Section: Layer-specific Ais Plasticitysupporting
confidence: 84%
“…Furthermore, studies in sensory cortices of various rodent species have outlined a layerspecific ability for plastic adaptation reflected by changes in spine dynamics, synaptic plasticity or direct stimulation responses both during development as well as at mature ages (Jiang et al, 2007;Skibinska et al, 2000;van der Bourg et al, 2017;van der Bourg et al, 2019). These studies showed that synaptic scaling and spine dynamics are a predominant feature of supragranular layers and to a much lesser extent for infragranular layers, underscoring our data showing layer-specific AIS plasticity.…”
Section: Layer-specific Ais Plasticitysupporting
confidence: 84%
“…5 , 6 ). The enhanced temporal resolution will be particularly useful for the analysis of neuronal activity during natural stimulus sequences and behaviors that occur on timescales shorter than typical durations of calcium transients, such as dynamical neuronal representations across theta cycles 52 or early and late phases of sensory responses in cortical areas 53 . Moreover, the inference of absolute spike rates will help improve the calibration of precisely patterned optogenetic manipulations 54 , 55 and the extraction of constraints, e.g., absolute spike rates, for computational models of neural circuits.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, local responses to single whisker deflection are already observed at P0, and they undergo progressive tuning, which is evidence of a segregated whisker map as early as P2-P3 (Mitrukhina et al, 2015). At the onset of active whisking (P14), localized cortical responses to single whisker deflections will undergo further layer-specific and temporal refinement (van der Bourg et al, 2017(van der Bourg et al, , 2019Yang et al, 2009). In vivo calcium imaging further confirms that the diameter of the domains reaches an average of 300 mm in the presumptive sensory cortices of neonatal rats and mice, whether spontaneous or evoked (Kummer et al, 2016;Nakazawa et al, 2020).…”
Section: Spontaneous Activity In the Developing Sensory Corticesmentioning
confidence: 97%